The Sanctification of Fear: Images of the Religious in Horror Films - Stone, Bryan P. (The journal of religion and film, 2001)
Horror film functions both as a threat and a catharsis by confronting us with our fear of death, the supernatural, the unknown and irrational, ''the other" in general, a loss of identity, and forces beyond our control. Over the last century, religious symbols and themes have played a prominent and persistent role in the on-screen construction of this confrontation. That role is, at the same time, ambiguous insofar as religious iconography has become unhinged from a compelling moral vision and reduced to mere conventions that produce a quasi-religious quality to horror that lacks the symbolic power required to engage us at the deepest level of our being. Although religious symbols in horror films are conventional in their frequent use, they may have lost all connection to deeper human questions.